The Stock Market Barometer - Hamilton, William Peter, 1867-1929 (New York John Wiley & Sons, 1998)
This pioneering classic in Dow Theory examines forecast value and trends within the stock market based on the Dow Theory of price movement. This finance classic offers tips and trends that William Hamilton observed over the years in the market, offering a view of market behavior that remains perpetually current.
Include Appendix
Keywords: Dow Jones Industrial Average -- Stock Price Forecasting -- Hamilton, William Peter, 1867-1929 -- Securities -- Speculation